2017
DOI: 10.1021/acs.molpharmaceut.7b00736
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Dual Cross-Linking of Neat Biogel with Controlled Mechanical and Delivery Properties

Abstract: Injectable biomaterials play a critical role in many biomedical applications. These materials, however, often have limitations in mechanical and drug-eluting properties attributed to their high water content and the weak secondary forces holding them together. Here we describe a new injectable material based on two complementary water-free, prepolymers modified with succinimidyl carbonate (SC) or with NH end groups that form a stiff matrix upon mixing. Cross-linking involves an immediate reaction between PEG-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Such a material would also interact with amine groups from embedded protein drugs. Moreover, they did not achieve controlled protein release over long periods of time . In a time frame of one day, the majority of the model protein bovine serum albumin was released for all different gel compositions.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Such a material would also interact with amine groups from embedded protein drugs. Moreover, they did not achieve controlled protein release over long periods of time . In a time frame of one day, the majority of the model protein bovine serum albumin was released for all different gel compositions.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, due to the absence of evaporating solvents, implants can also be prepared by 3D printing . Kelmansky et al have already shown that “neat biogels” can be prepared in a water-free manner through cross-linking with amine- and succinimidyl carbonate-functionalized 4armPEG2k precursors at 37 °C. , However, their material contained succinimidyl carbonate groups, that covalently bound to the tissue after injection. Such a material would also interact with amine groups from embedded protein drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An ideal bioadhesive should be liquid for ease of application but solidify quickly after administration . It should also maintain both adhesion and cohesion strength, biodegradability, elasticity, and biocompatibility .…”
Section: Introductionmentioning
confidence: 99%